Abdominal impacts of handlebar injuries in the PIPER child model: a prevention study - Arneitz, Christoph; Erlinger, Nico; Klug, Corina; Senica, Simone Oliver; Kuenzer, Thomas; Spitzer, Peter; Schalamon, Georg; Schalamon, Johannes (Frontiers in Public Health, 2024)
Aim Analysis of data from bicycle accidents reveals that handlebar impacts are a significant cause of injury, particularly among children. Despite existing safety regulations, such as helmet requirements, little attention is given to abdominal injuries. The aim of this study is to investigate the influence of handlebar ends on abdominal loading during bicycle crashes. Methods This study delves into the impact of five different handlebar designs on abdominal injuries during bicycle crashes, using finite element simulations with detailed Human Body Models (HBMs) of a six-year-old child (PIPER child model, Version 0.99.0). Four impact locations were identified in the injury scenario, selected according to the anatomical location of the most commonly injured organs, liver, pancreas, spleen and abdomen. Results Grip design features, such as shape and rigidity, significantly influence injury outcomes. Grips designed specifically for children demonstrate superior performance in reducing abdominal loading and injury metrics compared to standard grips. The highest injury potential was seen in a damaged handlebar end. Conclusion These findings underscore the importance of improved handlebar designs and standardized safety measures, especially for children. Implementation of such measures could mitigate the significant health and economic burden associated with handlebar-related injuries and enhance overall bicycle safety for children.